A forecast model for prevention of foodborne outbreaks of non-typhoidal salmonellosis - Rojas,Fernando; Ibacache-Quiroga,Claudia (PeerJ, 2020)
Background This work presents a forecast model for non-typhoidal salmonellosis outbreaks. Method This forecast model is based on fitted values of multivariate regression time series that consider diagnosis and estimation of different parameters, through a very flexible statistical treatment called generalized auto-regressive and moving average models (GSARIMA). Results The forecast model was validated by analyzing the cases of Salmonella enterica serovar Enteritidis in Sydney Australia (2014–2016), the environmental conditions and the consumption of high-risk food as predictive variables. Conclusions The prediction of cases of Salmonella enterica serovar Enteritidis infections are included in a forecast model based on fitted values of time series modeled by GSARIMA, for an early alert of future outbreaks caused by this pathogen, and associated to high-risk food. In this context, the decision makers in the epidemiology field can led to preventive actions using the proposed model.
Keywords: Forecast; GSARIMA model; Salmonella outbreaks; Surveillance